PENGARUH PEMBERIAN PUPUK ORGANIK CAIR NIRA AREN (Arenga pinnata MERR) TERHADAP PERTUMBUHAN TANAMAN KANGKUNG DARAT (Ipomea reptans POIR) - Lukman Arif (FAKULTAS PERTANIAN UNIVERSITAS ALKHAIRAAT, 2018)
This study aims to determine to determine the effect of land spinach plant growth due to the provision of liquid organic fertilizer palm sugar and to determine the right concentration of palm sugar palm POC to the growth of land spinach plants. This experiment used a single factor randomized block design consisting of 4 replications of 4 treatments. The best experimental results on plant height and number of leaves, leaf length and leaf width aged 14 and 24 HST were influenced by the use of palm juice 40 ml / L water with a height of 19.59 cm and 32.13 cm number of leaves 6.34 and 12.25 strands, leaf length 13.71 and 15.75 while leaf widths are 1.74 and 3.48 cm.